2022
DOI: 10.3390/reprodmed3020013
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Protocol for Post-Partum Salpingectomy with Suture Ligation: A Prospective Feasibility Study

Abstract: Our objective is to define a standard protocol for post-partum salpingectomy and provide a prospective assessment of safety and feasibility of such a procedure. Thus, a protocol for performing post-partum salpingectomy in limited-resource environments was created based on contemporary practices for tubal ligation. Gravidae presenting for post-partum tubal ligation following vaginal delivery or at time of cesarean were prospectively approached and, if consent was obtained, enrolled. Outcomes were compared to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Several studies have reported procedural risks of opportunistic salpingectomy immediately after vaginal delivery. 11,16,18,23 Opportunistic salpingectomy requires similar operative time, results in similar blood loss, and has similar rates of short-term postoperative complications compared with bilateral tubal ligation. 11,16,18 When energy devices are used, salpingectomy can be completed in shorter operative times relative to traditional methods of suture ligation, with improved surgeon satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported procedural risks of opportunistic salpingectomy immediately after vaginal delivery. 11,16,18,23 Opportunistic salpingectomy requires similar operative time, results in similar blood loss, and has similar rates of short-term postoperative complications compared with bilateral tubal ligation. 11,16,18 When energy devices are used, salpingectomy can be completed in shorter operative times relative to traditional methods of suture ligation, with improved surgeon satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…7 After these endorsements, this procedure was widely implemented into routine practice. [11][12][13][14] Opportunistic salpingectomy has been repeatedly demonstrated to be a safe alternative to a variety of standard tubal ligation methods across various surgical settings, including at the time of benign gynecologic surgery, during cesarean delivery, and in the immediate postpartum period, with similar surgical, reproductive, and hormonal outcomes. [14][15][16][17][18] Thus, the use of tubal ligation at vaginal delivery is decreasing in recent years in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation